The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/cc8914
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar fluid clearance in healthy pigs and influence of positive end-expiratory pressure

Abstract: IntroductionThe objectives were to characterize alveolar fluid clearance (AFC) in pigs with normal lungs and to analyze the effect of immediate application of positive end-expiratory pressure (PEEP).MethodsAnimals (n = 25) were mechanically ventilated and divided into four groups: small edema (SE) group, producing pulmonary edema (PE) by intratracheal instillation of 4 ml/kg of saline solution; small edema with PEEP (SE + PEEP) group, same as previous but applying PEEP of 10 cmH2O; large edema (LE) group, prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…Using transpulmonary thermodilution in pigs, Garcia-Delgado et al (21) found a slightly higher rate of decrease in EVLWI under levels of positive end-expiratory pressure similar to the ones we used. Using transpulmonary thermodilution in pigs, Garcia-Delgado et al (21) found a slightly higher rate of decrease in EVLWI under levels of positive end-expiratory pressure similar to the ones we used.…”
Section: Discussionsupporting
confidence: 71%
“…Using transpulmonary thermodilution in pigs, Garcia-Delgado et al (21) found a slightly higher rate of decrease in EVLWI under levels of positive end-expiratory pressure similar to the ones we used. Using transpulmonary thermodilution in pigs, Garcia-Delgado et al (21) found a slightly higher rate of decrease in EVLWI under levels of positive end-expiratory pressure similar to the ones we used.…”
Section: Discussionsupporting
confidence: 71%
“…Patients suffering from a high-grade AFC impairment in early ARDS have significantly higher mortality rates [4]. The present model implies a sustained effect of the TIP peptide on the initial alveolar flooding, which, in the absence of recruitment or PEEP [18], is consistent with a resolution of oedema fluid. Hence, an early enhancement of the alveolar fluid clearance may not only reduce the lung water content but also lead to more homogenous lung tissue.…”
Section: Discussionmentioning
confidence: 66%
“…Mechanical ventilation and the applied PEEP are also presumed to play an important role in pulmonary edema formation, but the empirical results are conflicting. Some studies show that the application of high PEEP causes more pulmonary edema formation and lung damage [27][28][29], whereas others show that higher PEEP results in less pulmonary edema by increasing alveolar fluid clearance [30]. These conflicting results reflect the complexity of the mechanisms underlying pulmonary edema formation.…”
Section: Discussionmentioning
confidence: 97%